Asuhan Kebidanan Pada Keluarga TN“A” Khususnya NY“M” Dengan Anemia Ringan Pada Trimester III di Dusun Aik Are Desa Ubung Lombok Tengah - Mariati Mariati; Baiq Reni Pratiwi; Baiq Sri Sulanti (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Background: Anemia is a condition that describes the total number of red blood cells that operate to carry oxygen has decreased to meet the body's physiological needs. Pregnant women are said to be anemic if their hemoglobin (Hb) level is <11g/dL. Anemia in pregnant women is caused by lack of intake of iron-rich foods, lack of vitamin C intake, short pregnancy intervals (parity). Objective: To carry out midwifery care for Mrs M G1P0A0H0, 25 years old, 30-31 weeks pregnant with a mild case of anemia. Methodology: with a midwifery care approach, namely SOAP which includes subjective, objective, assessment, plan, and implementation and evaluation sheets, carried out on 09 September 2024 to 23 September 2024 at the patient's house in Aik Are Hamlet, Ubung Village, Jonggat District. The results of the midwifery care that was carried out on Mrs M G1P0A0H0, 25 years old, 30-31 weeks pregnant with mild anemia, were carried out by giving Fe blood supplement tablets, Vitamin C, Vitamin B complex, and Calcium lactate. After 1 week of midwifery care, the mother experienced improvement. Hb 11.3 gr/dL and no discrepancy was found between theory and case. Conclusion: There was an increase in Hb in pregnant women after consuming Fe tablets, vitamin B complex, Vitamin C, and Calcium lactate for 1 week. Health workers are expected to be able to carry out health promotions about the importance of consuming Fe tablets, Vitamin C, Vitamin B complex, and Calcium lactate to increase iron absorption in the body.